The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5812/jjm.8584
|View full text |Cite
|
Sign up to set email alerts
|

Replication Efficiency of Influenza A Virus H9N2: A Comparative Analysis Between Different Origin Cell Types

Abstract: Background: Efficient isolation and detection of low pathogenic avian influenza viruses from surveillance samples continues to be a high priority. Currently, the new cell lines are considered for supporting the replication to high virus strains titers. Objectives: The replication efficiency of a low pathogenic avian influenza virus in different origin cells was evaluated under different conditions. Materials and Methods: Chicken embryo fibroblast (CEF) cell and human alveolar epithelial cell line (A549) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…However development HA-based vaccine is often difficult to attain due to emergence variants that have undergone sufficient antigenic drift in HA1 globular head to evade existing antibody responses. 13,14 It has been shown that HA2 is highly conserved as compared to HA1 subunit and antibodies recognizing stalk domain of the subunit neutralize the virus and provide sufficiently protection against infection and do cross-react with the HA of other subtypes. [15][16][17] Generally enhanced and directed immune responses to viral vaccine can be achieved by using adjuvants.…”
Section: Introductionsupporting
confidence: 89%
“…However development HA-based vaccine is often difficult to attain due to emergence variants that have undergone sufficient antigenic drift in HA1 globular head to evade existing antibody responses. 13,14 It has been shown that HA2 is highly conserved as compared to HA1 subunit and antibodies recognizing stalk domain of the subunit neutralize the virus and provide sufficiently protection against infection and do cross-react with the HA of other subtypes. [15][16][17] Generally enhanced and directed immune responses to viral vaccine can be achieved by using adjuvants.…”
Section: Introductionsupporting
confidence: 89%
“…Trypsin causes large nonspecific loss of viruses' infectivity under incubation conditions similar to FX. Thus, the factor is much more effective and specific in cleavage activation than in trypsin (13,25). The potential of FX to cleave HA and promote replication of influenza viruses is confirmed by our study in which maximum viral titers were reached one day earlier in MDCK/FX with comparative MDCK cells.The impact of FX on H9N2 virus replication kinetics upon engineered expression in BHK-21 cell line has been evaluated (16).…”
Section: Discussionsupporting
confidence: 64%
“…Proteolytic activation of HA is essential for the entry of influenza viruses into the target cells, and also to trigger the dynamic infectivity process. The HA cleavage site of H9N2 viruses is a monobasic motif, which is cleaved extracellularly by trypsin, and trypsin-like proteases in the cells lining the respiratory tract, resulting in localized infections ( 1 , 2 , 17 ). In addition to those enzymes, plasminogen, a blood-derived protease, may cleave HA of influenza viruses and promote replication of the viruses outside respiratory tissues ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%